Algorithmic Competition and Legal (In)Transparency: What Is the Reach of the Current Legal Framework of the EU? - Primec, Andreja (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The increasing use of artificial intelligence in digital markets introduces new dimensions to competitive relationships. It raises questions about the ability of the existing legal framework to respond to these challenges adequately. While algorithms can increase efficiency and predictability in the market, they also allow for tacit coordination, algorithmic coordination and potential abuses of dominance - often without direct human intent or classical evidence of collusion. The chapter addresses whether the current EU competition law rules - in particular, Articles 101 and 102 TFEU - and the new EU legislative instruments on artificial intelligence contain sufficient solutions to the emergence of algorithmic competition. Drawing on doctrinal perspectives and using classical methods of legal research, in particular the teleological and endogenous comparative methods, it evaluates existing legal institutions and highlights areas where additional legal solutions or more innovative interpretative approaches are needed in practice.